Around ecology and faith: Religious Hiking and Environmental Sustainability in southern Peruvian, annex of Chapi, Polobaya -Arequipa - Felipe Mario Zapata Delgado (2020)
The purpose is to know the impact that exists between religious hiking and environmental sustainability in the annex of Chapi, Polobaya. The displacement of people to the places that become sacred is a routine event in the world as it attracts attention, charm and mystery of what is considered inexplicable and magical, that is, to understand the peculiarities of the pilgrimage to the sanctuary of Chapi and which is what leads the pilgrims to make walks and ecotourism activities in order to reach the coveted sanctuary; and on the other hand, note that if the risks of these transfers have been weighed against the environmental framework, that is, if there is an ecological proposal to understand the carrying capacity of the Chapi area. The methodology is mixed, the testimonies of travelers and merchants are privileged through a survey that had a sample of 277 visitors to the Chapi festival, in high season. The results are evidenced in that 62% of visitors consider that the level of development of religious hiking in Chapi is regular and 37% consider it inappropriate, which indicates that religious activity is not developing in an environmentally appropriate way; In terms of environmental sustainability, 63% of visitors consider it bad, and 39% indicate that it is regular, which is why adequate environmental management is required in the commercial area, water sources and sanctuary